Prototype Control of Lighting Equipment Using Web-Based Arduino Microcontroller - Afif Rafyan; Ritzkal Ritzkal; Yuggo Afrianto (Jurnal Mantik, 2020)
Control of lighting equipment still uses the conventional way, namely by turning it on and off via a manual switch with the presence of light equipment control. It makes it easy for users to monitor or control lights anytime and anywhere with a note that the light equipment control will be applied using a WEB-based arduino microcontroller. From that background. remote control system, makes it easier for users to control and monitor room lights that are quite far away by conducting 4 stages of research (i) System Performance Analysis and Requirements Analysis (ii) Hardware Design Design, Schematic Design, Database Design, WEB Design, Topology Network (iii) Hardware Implementation and Software Implementation (iv) Testing. The results of this study are in the form of a control and monitoring system using a predetermined use with a system using the WEB. When the light is on, it will appear on the WEB which will become a printable report.